Effect of antiepileptic drugs on metrazol convulsions during ontogenesis in the rat - Mares, P; Maresová, D; Schickerová, R (Physiologia Bohemoslovaca, 1981)
The effect of ethosuximide, dipropylacetate and clonazepam on metrazol convulsions induced by a dose of 80 mg/kg was studied in 314 male albino rats aged from 5 days to adult. In a standard dose of 125 mg/kg, ethosuximide reliably protected only adult and 25-day-old rats, i.e. the age groups in which a mature minimal seizure was the only type of convulsion induced; in younger animals, not even a much higher dose (tested in 12-day-old rats) afforded reliable protection. Dipropylacetate and clonazepam had a manifest protective effect in all age groups, irrespective of the type of seizure. Isolated myoclonic jerks were less sensitive to antiepileptics and only dipropylacetate blocked them in the youngest age groups. In 21-day-old and older animals dipropylacetate induced stereotype head movement reminiscent of the serotonergic stereotypy described in the literature.
Keywords: Pentylenetetrazole; záchvaty; Rats; Clonazepam; antikonvulziva; mužské pohlaví; ethosuximid; Seizures; Valproic Acid; krysa rodu Rattus; věkové faktory; klonazepam; zvířata; Anticonvulsants; kyselina valproová; Age Factors; pentylentetrazol; Ethosuximide; Male; Animals